(untitled) - Schaefer, Richard T. (Boston, 2004)
1. Understanding sociology -- What is sociology? -- What is sociological theory? -- The development of sociology -- Major theoretical perspectives -- Developing the sociological imagination -- 2. Sociological research -- What is the scientific method? -- Major research designs -- Ethics of research -- Technology and sociological research -- 3. Culture -- Culture and society -- Development of culture around the world -- Elements of culture -- Culture and the dominant ideology -- Cultural variation -- 4. Socialization -- The role of socialization -- The self socialization -- Socialization and the life course -- Agents of socialization -- 5. Social interaction and social structure -- Social interaction and reality -- Elements of social structure -- Social structure in global perspective -- 6. Groups and organizations -- Understanding groups -- Understanding organizations -- Technology's impact on the workplace -- 7. The mass media -- Sociological perspectives of the media -- The audience -- The media industry -- 8. Deviance and social control -- Social control -- Deviance -- Crime -- 9. Stratification in the United States and worldwide -- Understanding stratification -- Stratification by social class -- Social mobility -- Stratification in the world system -- Stratification within nations : a comparative perspective -- 10. Racial and ethnic inequality -- Minority, racial, and ethnic groups -- Prejudice and discrimination -- Studying race and ethnicity -- Patterns of intergroup relations -- Race and ethnicity in the United States -- 11. Stratification by gender and age -- Social construction of gender -- Explaining stratification by gender -- Women : the oppressed majority -- Aging and society -- Explaining the aging process -- Age stratification in the United States -- 12. The family and intimate relationships -- Global view of the family -- Studying the family -- Marriage and family -- Divorce -- Diverse lifestyles -- 13. Religion and education -- Durkheim and the sociological approach to religion -- World religions -- The role of religion -- Religious behavior -- Religious organization -- Sociological perspectives on education -- Schools as formal organizations -- 14. Government, the economy, and the environment -- Economic systems -- Power and authority -- Political behavior in the United States -- Models of power structure in the United States -- The changing economy -- The environment -- 15. Population, health, and communities -- Demography : the study of population -- World population patterns -- Fertility patterns in the United States -- Sociological perspectives on health and illness -- Social epidemiology and health -- How did communities originate? -- Urbanization -- Types of communities -- 16. Social movements, social change, and technology -- Social movements -- Theories of social change -- Resistance to social change -- Technology and the
Keywords: Sociology,United States; Social conditions; 1980-